The Marketing Distribution Channels Development for Snake-Skined Gourami Through the Community Enterprise Networks Within Thailand Market - Meesubthong, Chatcharawan Meesubthong; Plaikaew , Kasem; Jonjoubsong , Lanthom; Kruta, Nuntawut (Business Administration and Management Journal Review, 2020)
The objective of this research is to study the current administration relative to the Conservation of the Bang Bo snake-skin gourami and processing community enterprise, Khlong Dan Sub-district, Bangbo District, Samutprakan Province, in order to pave the way of developing an enterprise management system as well as proposing possible distribution channels through community enterprise networks in different areas of Thailand. This research uses qualitative research methods. The main informants are 8 members of Bangbo Snakeskin Fish Processing Community Enterprise. The data collection techniques for this research include in-depth interview, participatory observation and focus group. For the quality of the research, the triangular method is applied in order to check the data. The results show that although there are a number of farmers raising and processing Bang Bo fish, it is reduced to just over 30 people this year. Group members of this research are in the production chain of snakeskin gourami both upstream, midstream and downstream. This plays an important role in driving large plots of snakeskin fish farmers with emphasis on raising and processing according to traditional conservation practices passed on from the generation to generation in the Khlong Dan Subdistrict, Bang Bo District. The Group focuses on using natural ingredients as the main ingredient and selling products at fair prices to manufacturers and consumers. However, the problem is that the lack of funds for operations causes obstacles for group development. For the distribution channels of the Conservation of Bangbo snake-skin gourami and processing community enterprise group, it is possible to distribute across three networks namely, Community Enterprise Networks in other areas, Thailand Post Company Limited and Huachiew Chalermprakiet University.